Deconvolution of electroosmotic flow in hysteresis ion transport through single asymmetric nanopipettes. Issue 23 (28th May 2020) - Brown, Warren; Li, Yan; Yang, Ruoyu; Wang, Dengchao; Kvetny, Maksim; Zheng, Hui; Wang, Gangli
Abstract : This report establishes a universal method to diagnose and deconvolute electroosmotic flow in nanoscale transport processes through current–potential measurements and analysis without simulation. Abstract : Unveiling the contributions of electroosmotic flow (EOF) in the electrokinetic transport through structurally-defined nanoscale pores and channels is challenging but fundamentally significant because of the broad relevance of charge transport in energy conversion, desalination and analyte mixing, micro and nano-fluidics, single entity analysis, capillary electrophoresis etc. This report establishes a universal method to diagnose and deconvolute EOF in the nanoscale transport processes through current–potential measurements and analysis without simulation. By solving Poisson, Nernst–Planck (PNP) with and without Navier–Stokes (NS) equations, the impacts of EOF on the time-dependent ion transport through asymmetric nanopores are unequivocally revealed. A sigmoidal shape in the I – V curves indicate the EOF impacts which further deviate from the well-known non-linear rectified transport features. Two conductance signatures, an absolute change in conductance and a 'normalized' one relative to ion migration, are proposed as EOF impact (factor). The EOF impacts can be directly elucidated from current–potential experimental results from the two analytical parameters without simulation. The EOF impact is found more significant in intermediate ionic strength, and potential and pore size dependent. The less-intuitive ionic strength and size dependence is explained by the combined effects of electrostatic screening and non-homogeneous charge distribution/transport at nanoscale interface. The time-dependent conductivity and optical imaging experiments using single nanopipettes validate the proposed method which is applicable to other channel type nanodevices and membranes. The generalizable approach eliminates the need of simulation/fitting of specific experiments and offers previously inaccessible insights into the nanoscale EOF impacts under various experimental conditions for the improvement of separation, energy conversions, high spatial and temporal control in single entity sensing/manipulation, and other related applications.